Efforts to Increase Public Knowledge About Health and the Use of Gadgets for Digital Marketing at RW 01 Babakan Ciparay Bandung City - Yogisutanti, Gurdani; Ardayani, Tri; Ekawati, Dian; Ngadiman, Susanna Theresia; Juliyanti, Juliyanti; Manan, Srihesty; Adhy Prasetyo, Yunus; Utari, Ardhini Dwi; Harun, Iriyanti (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service activities carried out by Working Group 1 Immanuel Bandung Health Institute in RW 01 Babakan Ciparay Village, Babakan Ciparay District, Bandung City. Community service aims to Increasing public knowledge about health and utilization gadgets for digital marketing at RW 01 Babakan Ciparay Bandung City. Activities involving 8 lecturers from the S1 Nursing, S1 Public Health, S1 Nutrition, D3 Nursing and D3 Hospital Service Management (MPRS) study programs. There were 10 students involved, consisting of 2 students from the S1 Kesmas Study Program, and 8 people from the D3 MPRS Study Program. Community service methods are carried out by means of counseling, lectures and questions and answers, using videos, posters, stickers, and direct practice. The media used are televisions, and laptops to display material in the form of power points. The material presented to the community was carried out in 2 stages and took place at the house of the head of RW 01 Babakan Ciparay. Phase 1 was held on Wednesday, September 8, carried out by 2 lecturers to deliver material on the use of gadgets in the era of digital marketing, family mental health and video screenings on the prevention of COVID-19, hypertension and diabetes mellitus. The second phase was held on Tuesday, 27 September 2022. The material presented includes: mental health of pregnant women and the importance of eating fruits and vegetables by means of lectures using power point media. Material on hypertension is delivered directly through lectures and questions and answers. Material on handling cardiac arrest at home, carried out with direct practice to the community. Media used for learning using mannequin aids. In addition, posters about COVID-19 prevention and stickers on how to sort waste were also given. The results of community service can increase public knowledge about health in general and the use of gadgets for digital marketing. The constraints of this community service activity have not been evaluated in a structured manner using questionnaires. The suggestion that can be recommended is that the implementation of community service be carried out in the same location with different materials, and that IKI should have a target area. Community service activities can then be continued with research first to find out the problems that exist in the community.